CRIMINALISTIC AND FORENSIC EXPERT SUPPORT FOR PROVING LABOR RIGHTS VIOLATIONS RELATED TO MOBBING AND DISCRIMINATION THEORETICAL METHODOLOGICAL AND JUDICIAL PERSPECTIVES - Tetiana V. Nikolaichuk; Аlona V. Bila (Alfred Nobel University Journal of Law)
The article is devoted to the criminalistic and forensic aspects of proving labor rights violations caused by mobbing and discrimination in the context of contemporary transformations in the labor environment. An interdisciplinary analysis is conducted regarding the problem of criminalistic and forensic support in proving violations of employees’ labor rights in cases involving mobbing and discrimination. The relevance of the study is driven by the growing number of court appeals concerning labor rights violations, particularly in the post-war period in Ukraine, the deterioration of the socio-psychological climate in workplaces, the digitalization of labor processes, and the lack of effective legal mechanisms for documenting and proving psychological violence and moral pressure, such as mobbing. The article substantiates the need to expand the evidentiary base by incorporating digital, psychological, behavioral, and documentary sources of information. In particular, the author highlights email correspondence, screenshots of messages in messengers, video surveillance data, psychological examination results, witness testimonies from colleagues, official documents, complaints, and other materials that may possess evidentiary value in court. The article explores the challenges of identifying mobbing as a legal phenomenon that currently lacks a clear legislative definition in Ukraine, which complicates its legal qualification and documentation in judicial proceedings. Approaches to expanding the methodological framework for forensic examinations in cases of labor rights violations resulting from mobbing and discrimination are proposed. The need for training specialists who possess knowledge in digital forensics, forensic psychology, and labor law is emphasized. Selected examples of judicial practice are analyzed, including decisions of national courts and the European Court of Human Rights, which confirm the fragmented nature of law enforcement in this area and demonstrate the underestimation of the potential of digital and psychological evidence. The article offers recommendations for improving the legal framework, developing methodological guidelines for judges and experts, establishing standards for documenting mobbing, and implementing specialized training programs for lawyers, psychologists, employers, and government officials to ensure appropriate responses to instances of discrimination and the protection of workers’ labor rights. Special attention is paid to the specifics of forming the evidentiary base in cases where violations are intangible, psychological, or digital in nature. It is found that traditional methods of documenting physical traces are not always suitable for proving mobbing, thus requiring the involvement of new methodologies and specialized knowledge in the fields of psychology, digital forensics, and labor law. Based on the analysis of judicial practice in Ukraine, typical errors in proving mobbing cases and the imperfections of court assessment mechanisms regarding digital and psychological evidence are identified. The article proposes ways to improve the methods of documenting and using evidence in such categories of cases, particularly through the implementation of an interdisciplinary approach and the adaptation of international experience.